2005
DOI: 10.3748/wjg.v11.i47.7461
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-4 and hepatocyte growth factor induce differentiation of human umbilical cord blood-derived mesenchymal stem cells into hepatocytes

Abstract: E L S E V I E R • BASIC RESEARCH •and HGF, and was higher (54.28±3.11 µg/L) on d 28 (t = 13.493, P <0.01). Albumin increased significantly on d 16 (t = 6.68, P <0.01) to 1.02±0.15 µg/mL, and to 3.63±0.30 μg/mL on d 28 (t = 11.748, P <0.01). Urea

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 31 publications
1
14
0
2
Order By: Relevance
“…MSCs from the three sources when submitted to the hepatocyte differentiation protocol lost fibroblastic morphology and acquired a polygonal shape, with a more prominent central nucleus, similar to normal hepatocytes, according to the results obtained by other authors [29,30,47].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…MSCs from the three sources when submitted to the hepatocyte differentiation protocol lost fibroblastic morphology and acquired a polygonal shape, with a more prominent central nucleus, similar to normal hepatocytes, according to the results obtained by other authors [29,30,47].…”
Section: Discussionsupporting
confidence: 79%
“…Selected genes were also not always the same, and, sometimes, gene expression was analyzed by means of different methods. Besides, the gene expression profile is not identical among all the hepatocytes [5,6,20,29,30,47,48].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Glycogen is secreted in differentiated cells starting from day 14 [6] or from days 24-28 [8]. In our experiments, solitary cells positively stained with Schiff reagent were detected after 7 days of differentiation.…”
Section: Resultsmentioning
confidence: 90%
“…Mature differentiated cells were characte ri zed by the presence of numerous granules in the cytoplasm [9]. Previous studies showed the appearance of small round cells among umbilical cord blood MSC after 1 week of differentiation [6]. By day 28, about 64% cells were small, round, epithelioid, while in the control all cells had a fi broblast-like shape.…”
Section: Resultsmentioning
confidence: 99%